Spatial and temporal variation in foraging of breeding red‐throated divers. (23rd April 2021) - Duckworth, J.; O'Brien, S.; Petersen, I. K.; Petersen, A.; Benediktsson, G.; Johnson, L.; Lehikoinen, P.; Okill, D.; Väisänen, R.; Williams, J.; Williams, S.; Daunt, F.; et al.
Abstract : Differing environmental conditions can have profound effects on many behaviours in animals, especially where species have large geographic ranges. Seasonal changes or progression through life history stages impose differential constraints, leading to changes in behaviours. Furthermore, species which show flexibility in behaviours, may have a higher capacity to adapt to anthropogenic‐induced changes to their environment. The red‐throated diver (RTD) is an aquatic bird, that is able to forage in both freshwater and marine environments, though little else is known about its behaviours and its capacity to adapt to different environmental conditions. Here, we use time‐depth recorders and saltwater immersion loggers to examine the foraging behaviour of RTDs from three regions across northwest Europe. We found that in the breeding season, birds from two regions (Iceland and Scotland) foraged in the marine environment, while birds from Finland, foraged predominantly in freshwater. Most of the differences in diving characteristics were at least partly explained by differences in foraging habitat. Additionally, while time spent foraging did not change through the breeding season, dives generally became more pelagic and less benthic over the season, suggesting RTDs either switched prey or followed vertical prey movements, rather than increasing foraging effort. There was a preference for foraging in daylight over crepuscular hours, with a stronger effect at two of the three sites. Overall, we provide the first investigation of RTD foraging and diving behaviour from multiple geographic regions and demonstrate variation in foraging strategies in this generalist aquatic predator, most likely due to differences in their local environment.